Agent-Based Virtual Humans in Co-Space: An Evaluative Study - Kang, Yilin; Tan, Ah-Hwee; Nah, Fiona Fui-Hoon (2012 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology, 2012)
Co-Space refers to interactive virtual environment modelled after the real world in terms of look-and-feel, functionalities and services. We have developed a 3D virtual world named Nan yang Technological University (NTU) Co-Space populated with virtual human characters. Three key requirements of realistic virtual humans in the virtual world have been identified, namely (1) autonomy: agents can function on their own, (2) interactivity: agents can interact naturally with players, and (3) personality: agents can exhibit human traits and characteristics. Working towards these challenges, we propose a brain-inspired agent architecture that integrates goal-directed autonomy, natural language interaction and human-like personality. We conducted an evaluative study involving human subjects to assess how virtual characters may enhance user experience in the virtual world. The results show that the fusion ART-based virtual humans receive significantly higher ratings in various performance measures related to user experience, especially Telepresence, Perceived Interactivity and Flow.